Karyotype of Brazilian Anopheles albitarsis sensu lato (Diptera:Culicidae). - Rafael, Míriam Silva (Genetics and Molecular Research, 2020)
Anopheles (Nyssorhynchus) albitarsis sensu lato is an important malaria vector in Brazil, especially in the Brazilian Amazon region. Chromosome preparations of fourth-instar larvae of A. albitarsis from Iranduba and Coari (AM) and Ilha Comprida (SP) were analyzed for karyotype determination and to improve cytogenetic identification of this species. Anopheles albitarsis possesses 2n = 6 chromosomes, with two pairs (submetacentric and metacentric) of autosomes and one pair of sex chromosomes, with X-Y dimorphism. The sex pair is homomorphic and acrocentric in females and heteromorphic in males, with a punctiform Y chromosome. Somatic pairing was detected in the prometaphase and metaphase chromosomes of the three A. albitarsis populations. Apparently, sex chromosome evolution in the Culicidae does not function as does evolution in the Culicidae, since it occurs in the subfamily Anophelinae, which possesses heteromorphic sex chromosomes and is regarded as primitive, based on several criteria. These karyotype data on the albitarsis complex reinforce the hypothesis that sex chromosome evolution in the subfamily Anophelinae is conserved, and the variation revealed in the mean size of chromosomes in three populations indicates that selective pressure in these populations is occurring only at a genetic level.